MEDIATING EFFECT OF MANAGEMENT INFORMATION SYSTEM (MIS): WAREHOUSE OPERATION EFFICIENCY IN SMALL AND MEDIUM ENTERPRISES (SMES) PERSPECTIVE (Journal of Technology and Operations Management, 2012)
This study investigates the relationship between the influential warehouse efficiency and warehousing operations, applied by the Small-Medium Enterprises (SMEs) manufacturing firms in Malaysia. These perspective research objectives are to determine whether there is any relationship between the warehousing operations, and warehousing Management Information System (MIS). It also examines the mediating effect of warehousing MIS in the relationship between warehousing attributes and warehouse efficiency. A quantitative method approach is applied in this research methodology. Three hypotheses have been proposed for the research with data collected from the survey of 182 SME manufacturing firm owners in Malaysia as listed in the SME Directory (2009). The findings indicate that the warehousing MIS significantly mediates and has an effect on the warehousing operations and their relationship with warehouse efficiency in the SME manufacturing firms. Theoretically, the research contributes to the growth development of the warehouse efficiency theories. Practically it could facilitate the owners or warehouse managers of the manufacturing firms in making the right management decisions regarding warehousing. As a conclusion, this study provides new knowledge and important insights of warehousing operations that will benefit manufacturing firms and other related industries, particularly for SMEs in Malaysia.